Asymptotic characterisation of regularised zero‐forcing receiver for imperfect and correlated massive multiple‐input multiple‐output systems - Ayed M. Alrashdi (IET Signal Processing)
Abstract In this work, the authors present an asymptotic high‐dimensional analysis of the regularised zero‐forcing receiver in terms of its mean‐squared error (MSE) and bit error rate (BER) when used for the recovery of binary phase‐shift keying (BPSK) modulated signals in a massive multiple‐input multiple‐output communication system. The asymptotic analysis is carried out when the system dimensions grow simultaneously large at a fixed ratio. The authors assume that the channel matrix is spatially correlated and not perfectly known. The authors use the linear minimum mean‐squared error (LMMSE) method to estimate the channel matrix. The asymptotic approximations of the MSE and BER enable us to solve various practical optimisation problems. Under MSE/BER minimisation, the authors derive (1) the optimal regularisation factor for RZF; (2) the optimal power allocation scheme. The numerical simulations match the derived asymptotic expressions, even when the problem dimensions are small.